O impacto da economia compartilhada nos mercados tradicionais: um recorte do Airbnb com os hotéis no Brasil - Bucciarelli, Bruno Barreto (2019)
It is a research that seeks to understand the impact that the shared economy causes in the traditional markets and, more specifically, the impact of Airbnb in the hotel chain. This topic is relevant because companies like Uber and Airbnb have only ten years of operation, have billions of billions, and have changed the way services are consumed. The data obtained will be extracted from the database of AirDna and the Forum of Hotel Operators in Brazil. These databases will be used for consolidating hotel and Airbnb information, respectively. Methodologically, a quantitative approach was chosen from secondary data. It is considered the Brazilian cities with the largest number of properties registered in Airbnb in the period between 2010 and 2016. The period was chosen because it is from 2010 that AirDna begins to collect Airbnb data. The data were treated by correlation multiple regression.